THE EFFECT OF PAD, SILPA, AND DBH ON CAPITAL EXPENDITURE WITH PDRB AS MODERATING VARIABLES IN PROVINCE GOVERNMENTS IN INDONESIA 2017-2020 - Syafnur, Ariza; Erlina, Erlina; Khaddafi, Muammar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The purpose of this study was to determine and analyze the effect of Regional Original Income (PAD), SiLPA, and DBH on Capital Expenditures with PDRB as a moderating variable in the Provincial Government in Indonesia. The population of this study is the Provincial Government in Indonesia as many as 34 provinces in the 2017-2020 observation year. The type of sample in this study uses a saturated sample where the entire population is sampled. The data was processed by using panel data regression statistical test with the help of SPSS software.The results of this study prove that PAD, SiLPA, and DBH have a simultaneous effect on capital expenditures. Partially PAD and SiLPA have a significant positive effect on Capital Expenditures, while DBH has no effect on Capital Expenditures. PDRB is not able to moderate the relationship between PAD, SiLPA, and DBH on Capital Expenditures.